Experimental Research on the Mechanical Properties of Methane Hydrate-Ice Mixtures - Yanghui Li; Yongchen Song; Weiguo Liu; Feng Yu (Energies, 2012)
The mechanical properties of methane hydrate are important to the stability of borehole and methane extraction from a methane hydrate reservoir. In this study, a series of triaxial compression tests were carried out on laboratory-formed methane hydrate-ice mixtures with various methane hydrate contents. Axial loading was conducted at an axial strain rate of 1.33%/min and a constant temperature of −10 °C. The results indicate that: (1) the deformation behavior is strongly affected by confining pressure and methane hydrate content; (2) the failure strength significantly increases with confining pressure when confining pressure is less than 10 MPa, and decreases with methane hydrate content; (3) the cohesion decreases with methane hydrate content, while the internal friction angle increases with methane hydrate content; (4) the strength of ice specimens are higher than that of methane hydrate-ice mixture specimens; Based on the experimental data, the relationship among failure strength, confining pressure and methane hydrate content was obtained, and a modified Mohr-Coulomb criterion considering the influence of methane hydrate content on shear strength was proposed.